Attenuation of IFITM proteins’ antiviral activity through sequestration into intraluminal vesicles of late endosomes - Prikryl, David; Zhang, You; Verma, Smita; Melikyan, Gregory B. (Frontiers in Immunology, 2025)
IntroductionInterferon-induced transmembrane proteins (IFITMs) inhibit the entry of diverse enveloped viruses. The spectrum of antiviral activity of IFITMs is largely determined by their subcellular localization. IFITM1 localizes to and primarily blocks viral fusion at the plasma membrane, while IFITM3 prevents viral fusion in late endosomes by accumulating in these compartments. We and others have previously shown that cyclosporine treatment relieves the fusion block for the Influenza A virus, but the mechanism of this rescue remained unclear.ResultsHere, we report the existence of at least two distinct pools of IFITMs in cyclosporine treated cells. Major pools of IFITM1 and IFITM3 were found in endosomes, with IFITM1 relocating from the plasma membrane by a mechanism involving macropinocytosis, while the newly synthesized IFITMs were trapped in the Golgi. We noted that cyclosporine-mediated IFITM redistribution to late endosomes was not associated with its degradation. Importantly, cyclosporine treatment restricted antibody access to the cytoplasmic N-terminus but not to the extracellular C-terminus of IFITMs, consistent with IFITM sequestration in intraluminal vesicles of late endosomes. Indeed, super-resolution microscopy revealed that cyclosporine induces IFITM3 redistribution from the periphery to the interior of late endosomes.DiscussionTogether, our results imply that IFITMs relocate to intraluminal vesicles of late endosomes in the presence of cyclosporine, thereby enabling viral fusion with the limiting membrane of these compartments. Our findings highlight the critical role of IFITM trafficking in antiviral defense and suggest a novel mechanism through which cyclosporine modulates the cell’s susceptibility to viral infections.